Customer flow, intermediaries, and the discovery of the equilibrium riskfree rate - Albert J. Menkveld; Asani Sarkar; Michel van der Wel (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
Macro announcements change the equilibrium riskfree rate. We find that treasury prices reflect part of the impact instantaneously, but intermediaries rely on their customer order flow in the 15 minutes after the announcement to discover the full impact. We show that this customer flow informativeness is strongest at times when analyst forecasts of macro variables are highly dispersed. We study 30 year treasury futures to identify the customer flow. We further show that intermediaries appear to benefit from privately recognizing informed customer flow, as, in the cross-section, their own-account trade profitability correlates with access to customer orders, controlling for volatility, competition, and the announcement surprise. These results suggest that intermediaries learn about equilibrium riskfree rates through customer orders.
urn:nbn:de:hebis:30-62269
Keywords: G14; E44; 330; Riskfree Rate; Macroeconomic Announcements; Customer Flow; Intermediary; Treasury Futures; Börsenkurs; Öffentliche Anleihe; Wertpapierhandel; Informationsverhalten; Ankündigungseffekt; Makroökonomischer Einfluss; USA